Comparison of arthroscopy-assisted versus open reduction and fixation for treating scaphoid fractures - Xiaolong Du; Xuehai Ou; Jidong Liang; Chao Liu; Qianjin Zheng; Shaoyan Shi (BMC Surgery)
Abstract Objectives Scaphoid fractures represent the most common type of carpal fracture. This study aimed to retrospectively evaluate and compare the therapeutic efficacy of wrist arthroscopy-assisted fixation versus conventional open reduction with fixation for scaphoid fractures. Methods We conducted a retrospective cohort study involving 159 patients with acute scaphoid fractures. Participants were stratified into two groups: the open reduction with fixation group (underwent open reduction and fixation) and the Arthroscopy group (received wrist arthroscopy-assisted fixation). Comparative analyses included operative duration, hospitalization length, fracture union time, and Visual Analog Scale (VAS) pain scores. Wrist functionality and range of motion were assessed using the Mayo wrist joint function scoring scale. Additionally, patient satisfaction was evaluated through a standardized questionnaire. Results Following propensity score matching (PSM), 54 matched pairs were analyzed. Baseline characteristics showed no significant intergroup differences. The Arthroscopy group exhibited statistically superior outcomes, including shorter operative time, reduced hospitalization, accelerated fracture union, and lower postoperative VAS scores. Mayo Wrist Scores were significantly higher in the Arthroscopy group, indicating better functional recovery. Furthermore, the Arthroscopy group demonstrated a lower overall complication rate and significantly improved scores in both physical and psychological assessment domains. Conclusions Wrist arthroscopy-assisted fixation significantly enhances postoperative recovery, yielding superior functional outcomes, reduced complications, and higher patient satisfaction compared to the open reduction with fixation group. This technique represents a promising approach for optimizing scaphoid fracture management.